RFID based mobiles: Next generation applications - Sharma, Meenakshi; Siddiqui, Adil (2010 2nd IEEE International Conference on Information Management and Engineering, 2010)
The boom of RFID usage -especially in logistics-has taken down the prices of RFID components and therefore opened also possibilities for other business fields to benefit the advantages of RFID. The technology for radio frequency identification (RFID) enables data to be transmitted by a tiny portable device, called a tag, which is read by an RFID reader and processed according to the needs of a particular application. It is only recently that the technology has begun to take off in the mass market. RFID applications in mobile phone business have not yet been deployed in other that small scale, but the discussion around this topic has been really started. Analysts predict that RFID will revolutionize areas of industry, such as supply chain management and the retail business, for example by reducing costs with better stock management. As the components for RFID-systems - tags and readers - have become smaller and cheaper, the technology has begun to take-off, in a variety of different areas This paper focuses on the applications of RFID technology in mobile telecommunication services. Many experts see RFID as an enabler for ubiquitous computing - the integration of computation into the environment: any device, anytime, anywhere. Reservation could be as simple as holding your phone close (less than 20 centimeters) to a poster or advertising billboard. RFID enabled mobile phones could be a first step in this direction. The combination of mobile phones and RFID technologies promises great potential in the market for mobile telecommunication services, which is discussed in this paper.